2021
DOI: 10.1039/d0ra10181h
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of N,N-dimethylformamide electrochemical oxidation using a Ti/RuO2–IrO2 electrode

Abstract: DEMS as an emerging technology was used to investigate the degradation mechanism of DMF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…This is in close agreement with Pasalari and his co-researchers who found that no biodegradability would be promoted in terms of sCOD in the EO process when the current density reached 30-40 mA/cm 2 (Pasalari et al 2021). It is important to understand that the restriction of current density is necessary as voltage increases, heat would be dissipated leading to other side effects (Hu et al 2021). Not only that, the operating conditions of the EO pre-treatment should be applied to help in solubilizing the organic matter in order to enhance biodegradability and overcome the hydrolysis problem in AD.…”
Section: Effect Of Current Densitysupporting
confidence: 88%
See 1 more Smart Citation
“…This is in close agreement with Pasalari and his co-researchers who found that no biodegradability would be promoted in terms of sCOD in the EO process when the current density reached 30-40 mA/cm 2 (Pasalari et al 2021). It is important to understand that the restriction of current density is necessary as voltage increases, heat would be dissipated leading to other side effects (Hu et al 2021). Not only that, the operating conditions of the EO pre-treatment should be applied to help in solubilizing the organic matter in order to enhance biodegradability and overcome the hydrolysis problem in AD.…”
Section: Effect Of Current Densitysupporting
confidence: 88%
“…Based on the regression equations, there was an immediate positive effect between both the independent factors and the performance of dependent variables whereby the increase in the independent variable was able to improve the performance and vice versa (Moteshaker et al 2020). Through the comparison of the coefficients among the regression equations in linear term, it helps to identify the relative impact of the variables (Hu et al 2021). In this study, the coefficient of current density (A) had achieved the highest value among the predictor variables in terms of MLVSS removal, CST reduction and sCOD increment of 14.66, 20.07 and 15.28, respectively.…”
Section: Rsm Type Ccd Optimizationmentioning
confidence: 99%
“…Ir deposition could improve the uniformity and stability of RuO 2 /Ti electrodes. [105] Mixed metal oxide electrodes exhibit dense structures with higher electrocatalytic activity, [106] such as Ti/IrO 2 -RuO 2 [97,[107][108][109] , Ti/SnO 2 -RuO 2 , [110,111] Ti/RuO 2 -IrO 2 -SnO 2 , [112] Ti/RuO 2 -IrO 2 -TiO 2 [113] etc., which have been widely used in the treatment of refractory pollutants with high degradation efficiency. The Ti/SnO 2 -Sb 2 O 5 -IrO 2 -RuO 2 mixed oxide anode prepared by Liu et al [114] was used to electrochemically destruct the targeted pharmaceuticals, and the electrode showed higher OEP, lower chlorine evolution potential, larger active area, and higher stability.…”
Section: Ti/ruo 2 Electrodementioning
confidence: 99%
“…It is noteworthy that a recent study on the mechanism of anodic oxidation of DMF using different electrodes, current density, pH and NaCl, is described in [19b] …”
Section: Mechanismmentioning
confidence: 99%